Students' Grit and Their Post-Compulsory Educational Choices and Trajectories: Evidence from Switzerland - Janine Albiez; Maurizio Strazzeri; Stefan C. Wolter (CESifo GmbH, 2024)
We examine the association between the personality trait grit and post-compulsory educational choices and trajectories using a large survey linked to administrative student register data. Exploiting cross sectional variation in students' self-reported grit in the last year of compulsory school, we find that an increase in students' grit is associated with a higher likelihood to start a vocational education instead of a general education. This association is robust to the inclusion of cognitive skill measures and a comprehensive set of other students' background characteristics. Moreover, using novel data on skill requirements of around 240 vocational training occupations, we find that grittier vocational education students sort into math-intensive training occupations. Similarly, students in general education with more grit select themselves more often into the math-intensive track. Finally, we do not find evidence that students with a higher grit have lower dropout rates in post-compulsory education.
Keywords: D01; I20; 330; non-cognitive skills; personality traits; grit; educational choices